Budaya Politik Masyarakat dalam Mendukung Implementasi Program Bantuan Sosial di Kelurahan Rantau Indah Kabupaten Tanjung Jabung Timur - Fitria Alha; Nasuhaidi Nasuhaidi; Aditya Romadhon; Dimas Subekti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the political culture of the community in supporting the implementation of social assistance programs in Rantau Indah Village, Tanjung Jabung Timur Regency. This research employed a descriptive qualitative approach to understand community political culture through cognitive, affective, and evaluative orientations toward social assistance programs. Data were collected through interviews, observations, and documentation involving village officials, RT/RW leaders, and social assistance beneficiaries. The findings indicate that community political culture plays an important role in supporting the implementation of social assistance programs. In the cognitive aspect, most people understand the existence and objectives of social assistance, although some still have limited understanding of beneficiary criteria. In the affective aspect, the community shows trust in village officials despite perceptions of inequality in aid distribution. Meanwhile, the evaluative aspect reflects community participation in supervision and feedback. Overall, community political culture tends to be participatory in supporting social assistance implementation. The study also reveals that transparent communication, active community involvement, and accountability of village authorities contribute significantly to strengthening public trust and improving the effectiveness of program implementation. Community participation in monitoring and evaluating the distribution process helps minimize potential conflicts and encourages greater transparency. These findings suggest that strengthening political awareness, enhancing public access to information, and promoting participatory governance are essential to ensure that social assistance programs are implemented fairly, effectively, and sustainably while improving community welfare and reinforcing good local governance practices.